HER2 positivity may confer resistance to therapy with paclitaxel in breast cancer cell lines. (3rd April 2018) - Haghnavaz, Navideh; Asghari, Faezeh; Elieh Ali Komi, Daniel; Shanehbandi, Dariush; Baradaran, Behzad; Kazemi, Tohid
Abstract: Introduction: MicroRNAs (miRNAs) are short non-coding single-stranded RNAs. Involving in post-transcriptional gene silencing, miRNAs are thought to play important roles in many cancers such as breast cancer. Paclitaxel is used widely in the treatment of breast cancer. In this study, we investigated the effect of paclitaxel treatment on the expression levels of two oncomirs (oncomiRs), miR-21 and miR-203, in breast cancer cell lines. Materials and methods: MTT assay was performed to determine IC50 of paclitaxel for human breast cancer cell lines including MCF-7, MDA-MB-231, SKBR3 and BT-474. After RNA extraction and cDNA synthesis, the expression levels of miRNAs were then quantitatively evaluated using real-time PCR. Results: Our results showed that after treatment, the expression levels of both miR-21 and miR-203 were significantly increased in HER2-positive cell lines, BT-474 and SKBR3. HER2-negative cell lines, MCF-7 and MDA-MB-231, in contrast had significantly decreased expression of both assessed oncomiRs. Conclusion: Our results showed that the expression levels of oncomiRs were increased in HER-2 positive breast cancer cells and this finding is in line with previous studies. Our findings present a probable mechanism of resistance against paclitaxel chemotherapy in HER2-positive breast cancers.